ORIENTASI DAN PENANAMAN TANAMAN UPAKARA DI ASHRAM GANDHI PURI DESA PAKSEBALI KECAMATAN DAWAN KABUPATEN KLUNGKUNG - Suwantana, I Gede; Subagia, I Nyoman; Sudiana, I Gusti Ngurah; Surada, I Made; D.E, Relin (Sevanam: Jurnal Pengabdian Masyarakat, 2022)
The existence of upakara plants in Bali is increasingly rare. This happens because of the increasingly massive implementation of the ceremony and the community is less concerned about its preservation. On that basis, it is very urgent to plant upakara plants in Bali because in addition to supplying the need for ceremony materials, it is also a form of environmental preservation or conservation of rare plants. This work describes how the scarcity of these plants is along with the efforts to be made to overcome them. One effort that can be done is by replanting and then inspiring everyone to realize that planting upakara plants both in the yard and in the form of a gumi banten garden is very important. Bali will look beautiful if this upakara plant is planted in every yard because it also acts as an ornamental plant. I Gusti Bagus Sugriwa's Doctoral Program at UHN, through community service, seeks to inspire the youth at the Gandhi Puri Ashram about the importance of this upakara plant and directly plant upakara plants at the Ashram location. Through this program, it is hoped that the land in the Gandhi Puri Ashram will be overgrown with various types of upakara plants and the awareness of the residents to actively plant upakara plants and inspire others to actively contribute to preserving the rarer upakara plants.